(3KhQI CSYGQ GdfaWs - (3VjGA eLjO(B, (3GdehShjs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2004)
(3GdCQbGe GdbjGSjI dCSYGQ GdfaW NdGd GdaJQI ef(B1(3LhGf(B-16(3CcJhHQ(B2004(3,RjGOI GdWdH GdYGdej Ydi GdfaW YGe (B2004(3,efXeI ChHc JJLGhH eY GdWdH GdYGdej GdeJRGjO Ydi GdfaW,GdSYQ GdYGOd ddfaW hChHc ZjQ eSDhdI Yf GQJaGY CSYGQ GdeTJbGJ GdfaWjI aj CeQjcG hChQhHG,CKQ EQJaGY CSYGQ GdfaW Ydi eYOd Gdfeh GdEbJUGOj GdYGdej,CgejI faW GdTQb GdChSW hGdMQH Ydi GdYQGbs
(3HHdjhZQGajG(B:(3U U(B.110-111s
Keywords: (3GdHJQhds